'Songs You Need to Hear': Public radio partnerships and the mobility of national music. (1st April 2017) - Fauteux, Brian
Public radio broadcasters are mandated to act as vehicles for supporting and promoting national culture, including music. Despite a predominately national focus, the Canadian Broadcasting Corporation has partnered with public broadcasters from other nations in a song-sharing initiative called 'Songs You Need to Hear'. The initiative includes a monthly blog post with embedded audio and brief descriptions of the music by radio hosts from CBC (Canada), BBC (UK), NPR (US), ABC (Australia), and RTÉ (Ireland). This article explores the ways in which a mobile, transnational song-sharing project emerged between 2000 and 2015 and what it reveals about the pressures and new models developed in this period of digital transmission. 'Songs You Need To Hear' represents the current state of public media in which the need to digitize, globalize, and universalize, combined with unreliable funding models, has resulted in the treatment of music on the radio as inexpensive and highly accessible content that straddles the line between the global brand extension of public media institutions and ideas about the fundamental role of public media in their support of national culture.